(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has rapidly spread worldwide, leading to the COVID-19 pandemic. Understanding the host’s immunological response to SARS-CoV-2 infection is critical for finding effective treatments. Interleukin10 is an anti-inflammatory cytokine that control immune responses. However, its exact involvement in the context of SARS-CoV-2 infection severity is unknown.We conducted a systematic review and meta-analysis to understand better the association between SARSCoV-2 infection severity and IL-10 levels. A comprehensive search was conducted across various databases to identify relevant published research. The studies included analyses of IL-10 levels in COVID-19 patients, stratified by disease severity. The results of our investigations show a positive association between the severity of SARS-CoV-2 infection and IL-10 levels, indicating that IL-10 may play a role in disease etiology. More research is required to comprehend the molecular foundation of this association and to explore the therapeutic prospects of targeting IL-10 in COVID-19 treatment. Having this knowledge could help develop particular treatment plans for COVID-19 patients based on their immune profiles